Evaluasi Atas Kinerja Keuangan PT. Kereta Api Indonesia (Persero) Periode 2003-2008 Dengan Menggunakan Metode Analisis Rasio Keuangan Sistem DU-PONT - Sujai, Mahpud (Warta Penelitian Perhubungan, 2011)
This study aims to elaborate the financial ratios and assessing the financial performance of PT. Kereta Api Indonesia (Persero) during the period of 2003 through 2008 so it can be used to project the future financial condition. This study is a literature review and using qualitative methods to explore ways of collecting information through data in various types, mainly secondary data which is the financial statements of the PT. KAI. Analysis of financial statements used as a basis for assessing the performance of the financial statements is the Du-Pont methods of analysis. Based on the analysis conducted, results showed that from seven indicators were analyzed, only one indicator shows that the cbmpany' s financial performance improves. Meanwhile six other indicators shaw a deteriorating corporate performance. Because the financial performance of PT. KAI is still unsatisfied, PT.KAI must improve its financial performance by increasing sales, cost efficiency, increase corporate profits and seek new breakthroughs in improving corporate performance.Keywords: Financial Statements Analysis, Du-Pont System and PT. KAI (Persero)